PENGARUH SUBSIDI INPUT TERHADAP NILAI TUKAR PETANI PADI DI INDONESIA - Redy Prasetyo; R. N. Afsdy Saksono (Lembaga Administrasi Negara, 2020)
This study aimed to determine how impact of the agricultural input subsidy on farmer terms of trade in Indonesia. This study used a quantitative approach with survey method on time series data of each variable analyzed. Research variables were seed subsidy, fertilizer subsidy, paddy yield and farmer terms of trade. The data used are secondary data from 2009-2015. The analytical method employed was path analysis was applied to the analysis of the national data. The results of path analysis showed that at the national level, seed subsidies affect NTP negatively. Fertilizer subsidies analysis at the national level, also showed negative affect on NTP.Keywords: seed subsidy, fertilizer subsidy, productivity, farmer terms of trade, path analysis